Teachers’ Challenges and Strategies in Implementing Cooperative Learning in English Foreign Language Context - Sukarno; Ella Wulandari; Ainayya Nabilla (Universitas Muhammadiyah Jember, 2025)
Cooperative learning becomes an effective teaching and learning method if the teachers can face challenges by using appropriate strategies. This study aimed to describe the experiences of English teachers in implementing cooperative learning as a teaching and learning method. This study focused on most applicable cooperative learning methods, challenges, and strategies they used for overcoming the challenges itself. The researcher utilized qualitative methods with class micro-ethnography. Two English teachers selected by using purposive sampling with essential criteria applied ethical considerations. Employing a qualitative research design, data was gathered through semi-structured interviews consisting of six questions. The data were analyzed by utilizing thematic analysis. The result found that the participants could define the concepts of cooperative learning derived from their personal experiences. Both of them were focused on using Think-Pair-Share (TPS) as a cooperative learning method. All of the participants consistently answered TPS as the most important models to implement, applicable models, and the easiest model. Both of them had similarities and differences in answering challenges and strategies to overcome the difficulties they faced in the classrooms. The participants suggested exploring more Cooperative Learning models and practicing it into their English classrooms.